Critical Social Media Analysis: Problematising Online Policy Representations of the Impact of Imprisonment on Families - Ugwudike, Pamela (International journal of offender therapy and comparative criminology, 2024)
Drawing on the Foucauldian policy analysis framework developed by Bacchi (2009) and building on insights distilled from a study of discourses on the microblogging SNS, Twitter, this paper makes three novel contributions. It unravels how the impact of imprisonment on families is represented in or produced through policy discourses and other governance practices. It also demonstrates how SNS affordances enable affected families to resist and challenge the discourses and proffer alternatives strategies that can inform a transformational problematization model. The paper makes a third contribution by demonstrating how a methodologically innovative triangulation of computational and social science methods can be used to study the contributions of hard-to-reach populations such as the families of people in prison.